Indications and Relative Utility of Lower Endoscopy in the Management of Clostridium difficile Infection - Burkart, Nora E. (Hindawi Publishing Corporation, 2011)
Background. Diagnosis and management of Clostridium difficile infection (CDI) rely upon clinical assessments and diagnostic studies. Among diagnostic tests, lower gastrointestinal (GI) endoscopy in the setting of CDI remains controversial. Objective. To describe the role of lower endoscopy in CDI management. Methods. Retrospective study of lower endoscopies in CDI at four metropolitan hospitals, July 2005 through December 2007. Results. Of 1760 CDI inpatients, 45 lower endoscopies were performed on 43 patients. Most common indications were ruling out other etiologies (42%), inconclusive stool studies (36%), and worsening course (11%). Most endoscopies (73%) had positive findings, including pseudomembranous colitis (49%) and nonspecific colitis (24%). Biopsies were performed in 31 cases, more with nonspecific colitis (10/11, 92%) compared to pseudomembranous colitis (14/22, 64%). Conclusion. While not recommended as a primary screening tool, lower GI endoscopy can add valuable information in CDI when other colonic pathologies may exist, studies are inconclusive, or clinical status worsens.